Community outreach with registrar of society / Siti Nabilah Mohd Shaari - Mohd Shaari, Siti Nabilah (Corporate Communication Unit, Universiti Teknologi MARA, Perak Branch, 2018)
The aim of the workshop and dialogue session was to increase the submission rate of financial annual returns from societies and clubs in Perak via the online system called e-ROSES. The participants of this workshop consisted of the treasurer and secretary of each society or club. Through a briefing and a detailed hands-on consultation, they were guided on how to accurately classify the items that are subsequently needed to be keyed into the system. An accurate classification will enable the Registrar of Society to render accurate reports of the societies and clubs' activities.